An Adaptive Sliding Mode Controller for a PAM-based Actuator - Dao, Quy-Thinh; Dinh, Vuong Van; Vu, Chien Tuan; Pham, Thuyet Quang; Duong, Duc Minh (Engineering, Technology & Applied Science Research, 2023)
The Pneumatic Artificial Muscle (PAM) is a promising actuator for developing the human-robot interaction system. However, modeling and controlling PAM-based actuators are a significant difficulty due to the inherent uncertainty and hysteresis of PAM. Besides, the control approach of a PAM-based system also deals with unknown disturbances that always exist in any system. This study developed a sliding mode controller that employs an adaptive law to deal with issues and improve control performance. Furthermore, the stability of the proposed controller is proven based on the Lyapunov stability criterion. Finally, through a series of tests, the effectiveness of the proposed control approach is verified.